Human Papillomavirus in Patients With Hypopharyngeal Squamous Cell Carcinoma. (13th April 2021) - Patel, Evan J.; Oliver, Jamie R.; Jacobson, Adam S.; Li, Zujun; Hu, Kenneth S.; Tam, Moses; Vaezi, Alec; Morris, Luc G. T.; Givi, Babak
Abstract : Objective: Assess the testing rates and prognostic significance of human papilloma virus (HPV) status in hypopharynx malignancies. Study Design: Historical cohort study. Setting: National Cancer Database. Methods: Review of the National Cancer Database was conducted between 2010 and 2017 for squamous cell carcinomas (SCCs) of the hypopharynx. We investigated how often the tumors were tested for HPV and whether it was associated with survival outcomes. Results: A total of 13, 269 patients with hypopharynx malignancies were identified. Most cases were not tested for HPV status (n = 8702, 65.6%). Of those tested, 872 (19.1%) were positive for HPV and 3695 (80.9%) were negative. The proportion of nonoropharyngeal SCCs tested for HPV increased nearly every year during the study, with roughly one‐third of cases (31.9%) being tested in 2017. In the facilities classified as high‐testing centers of nonoropharyngeal SCCs of the head and neck, 18.7% of hypopharyngeal tumors were HPV positive. HPV‐negative status was associated with worse survival on multivariable analysis. In propensity score–matched analysis controlling for all factors significant in multivariable regression, 2‐year survival remained higher in the HPV‐positive cohort (77.7% vs 63.1%, P <. 001). Conclusions: HPV‐positive tumors constitute a sizable minority of hypopharynx tumors and are associated with improved survival. Expansion of HPV testing to hypopharynx malignancies may be warranted.